Child Care Subsidy Receipt, Employment, and Child Care Choices of Single Mothers - Erdal Tekin (Institute for the Study of Labor (IZA), 2004)
This paper examines the impact of actual subsidy receipt of single mothers on their joint employment and child care mode decisions in the post-welfare reform environment, which places a high priority on parental choice with the quality and type of care chosen. Results indicate that single mothers are highly responsive to child care subsidies by increasing their employment while moving from parental and relative care to center care in the process.
Keywords: I38; J13; 330; child care subsidy; employment; single mother; Frauenerwerbstätigkeit; Alleinerziehende; Arbeitszeit; Kinderbetreuung; Arbeitsangebot; Familienleistungsausgleich; Schätzung; Vereinigte Staaten